Microbiological assessment of the quality and safety of black African ostrich meat in accordance with the requirements of TR CU 021/2011 SanPiN 2.3.2.1078-01 - S. S. Pateev; Yu. N. Cherneta (Новые технологии)
Introduction. Microbiological assessment of the quality and safety of black African ostrich meat has been conducted.The goal of the research is to analyze the microbiological parameters of meat in order to confirm its compliance with sanitary standards and ensure safety for consumers. The study includes the determination of the total microbial count (QMAFAnM), the detection of coliform bacteria (CGB), and an analysis for the presence of pathogenic microorganisms such as Salmonella and Staphylococcus aureus.The research methods included determination of the total number of microorganisms (QMAFAnM) in accordance with the requirements of TR CU 021/2011 and SanPiN 2.3.2.1078-01, analysis for coliform bacteria (CGB) with inoculation of Kessler medium and subculture onto Endo medium, detection of Salmonella using buffered peptone water, RVS broth, MKT broth and subculture onto XLD and Endo media, as well as determination of Staphylococcus aureus using salt broth and subculture onto salt agar for microscopic examination of colonies.The research results have shown that all tested ostrich meat samples comply with safety standards and do not contain hazardous levels of microorganisms. The absence of pathogenic microorganisms and compliance with other microbiological indicators confirms the high quality of the meat and its suitability for use in food production. It has been concluded that black African ostrich meat meets modern food safety standards and can be used to develop functional and dietary food products. This also highlights the need for further research and promotion of ostrich meat as a safe and healthy product on the market.